Midbrain infarction: associations and aetiologies in the New England Medical Center Posterior Circulation Registry. Issue 3 (1st March 1998) - Martin, P J; Chang, H M; Wityk, R; Caplan, L R
Abstract : Most reports of midbrain infarction have described clinicoanatomical correlations rather than associations and aetiologies. Thirty nine patients with midbrain infarction (9.4%) are described out of a series of 415 patients with vertebrobasilar ischaemic lesions in the New England Medical Center Posterior Circulation Registry. Patients were categorised according to the rostral-caudal extent of infarction. The "proximal" vertebrobasilar territory includes the medulla and posterior inferior cerebellar artery territory. The "middle" territory includes the pons and anterior inferior cerebellar artery territory. The "distal" territory includes the rostral midbrain, thalami, superior cerebellum, and medial temporal and occipital lobes. Midbrain infarction was accompanied by "proximal" territory infarcts in four patients, and by "middle" territory infarction in 19 patients. Thirteen patients had associated "distal" territory infarcts, three of whom had occipital or temporal lobe infarcts. Only three patients had isolated midbrain infarcts. Cardioembolism (n=11), in situ thrombosis (n=9), large artery to artery embolism (n=7), and intrinsic branch penetrator disease (n=5) were the most common aetiologies. Bilateral infarction and accompanying pontine infarction were associated with the most extensive vertebrobasilar occlusive disease. Midbrain infarction was 10-fold more likely to be accompanied by ischaemia of neighbouring structures than it was to occur in isolation. Recognition of the different patterns of infarction may act as a guide to the underlying aetiology and vascular lesions.